Cerenkov Luminescence Imaging in the Development and Production of Radiopharmaceuticals - van Dam, R. Michael; Chatziioannou, Arion F. (Frontiers in Physics, 2021)
Over the past several years there has been an explosion of interest in exploiting Cerenkov radiation to enable in vivo and intraoperative optical imaging of subjects injected with trace amounts of radiopharmaceuticals. At the same time, Cerenkov luminescence imaging (CLI) also has been serving as a critical tool in radiochemistry, especially for the development of novel microfluidic devices for producing radiopharmaceuticals. By enabling microfluidic processes to be monitored non-destructively in situ, CLI has made it possible to literally watch the activity distribution as the synthesis occurs, and to quantitatively measure activity propagation and losses at each step of synthesis, paving the way for significant strides forward in performance and robustness of those devices. In some cases, CLI has enabled detection and resolution of unexpected problems not observable via standard optical methods. CLI is also being used in analytical radiochemistry to increase the reliability of radio-thin layer chromatography (radio-TLC) assays. Rapid and high-resolution Cerenkov imaging of radio-TLC plates enables detection of issues in the spotting or separation process, improves chromatographic resolution (and/or allows reduced separation distance and time), and enables increased throughput by allowing multiple samples to be spotted side-by-side on a single TLC plate for parallel separation and readout. In combination with new multi-reaction microfluidic chips, this is creating a new possibility for high-throughput optimization in radiochemistry. In this mini review, we provide an overview of the role that CLI has played to date in the radiochemistry side of radiopharmaceuticals.